2006
DOI: 10.1063/1.2159473
|View full text |Cite
|
Sign up to set email alerts
|

Orientation polarization from faster motions in the ultraviscous and glassy diethyl phthalate and its entropy

Abstract: Dielectric spectra of the ␤ relaxation in glassy and ultraviscous liquid diethyl phthalate show that its relaxation strength ⌬⑀ ␤ , the distribution of times, and the relaxation rate are more sensitive to temperature T in the ultraviscous liquid than in the glassy state. The ⌬⑀ ␤ against temperature plot has an elbow-shaped break near T g of ϳ181 K, which is remarkably similar to that observed in the entropy, enthalpy, and volume against temperature plots, and in the plot of ⌬⑀ ␤ against the liquid's entropy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…The initially slower increase in slope becomes more rapid as T g is approached on heating and reaches the slope for the liquid state. Similar relaxation features have been observed also for diethyl phthalate and there these were related to the configurational entropy [38].…”
Section: Jg Relaxation On Heating and Mimicry Of Thermodynamic Propersupporting
confidence: 69%
“…The initially slower increase in slope becomes more rapid as T g is approached on heating and reaches the slope for the liquid state. Similar relaxation features have been observed also for diethyl phthalate and there these were related to the configurational entropy [38].…”
Section: Jg Relaxation On Heating and Mimicry Of Thermodynamic Propersupporting
confidence: 69%
“…76 Finally, the dielectric and mechanical relaxation spectra and the fixed frequency isochrones have shown that the JG relaxation peak height (or strength) decreases when T f is decreased. 8,9,26,[40][41][42][43][44][45][46][47][48] One expects a qualitatively similar decrease of the strength of the JG endotherm. Though the approach to the plateau-like value at T < T g in the plots of Figs.…”
Section: Local-region Fluctuations and The Jg Endothermmentioning
confidence: 62%
“…This suggestion of course requires appropriate theoretical consideration, which is however beyond the scope of the present paper. It is also interesting to note that mentioned s 0 values are of the same order as values for relaxation times for dielectric b-relaxation [1][2][3][4].…”
Section: Discussionmentioning
confidence: 94%
“…Molecular motions in glassy supercooled liquids have been studied using dielectric relaxation [1][2][3][4], nuclear magnetic resonance (NMR) [4][5][6][7], electron paramagnetic resonance (EPR) [8][9][10][11], and many other techniques. However, the microscopic nature of the phenomenon of glass transition is still unclear.…”
Section: Introductionmentioning
confidence: 99%